2014
DOI: 10.4103/0301-4738.109521
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification without preoperative topical mydriatics: Induction and sustainability of mydriasis with intracameral mydriatic solution

Abstract: Context:Intracameral mydriatic solution can eliminate the disadvantages of repeated eye drop instillation regimen and provide adequate mydriasis for phacoemulsification with added advantages.Aims:Evaluating the role of intracameral irrigating solution (0.5% lignocaine + 0.001% epinephrine) in initiating and maintaining the pupillary mydriasis during phacoemulsification. Secondary aims were to observe the effect of surgical time, nucleus density and ultrasound time on mydriasis during the procedure.Settings and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(39 reference statements)
2
10
1
Order By: Relevance
“…The average surgical time in our study was 18 minutes, which is more than that of the studies by Nikeghbali et al, Gupta et al, and Joshi et al23,29,33 The average surgical time noted by Joshi et al in age-related cataract was 6.913±4.45 minutes, wherein patients with nondilating pupils and diabetic cataracts were excluded. We could not compare our surgical time, as there is no literature available on the use of only intracameral lignocaine in patients with cataract with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The average surgical time in our study was 18 minutes, which is more than that of the studies by Nikeghbali et al, Gupta et al, and Joshi et al23,29,33 The average surgical time noted by Joshi et al in age-related cataract was 6.913±4.45 minutes, wherein patients with nondilating pupils and diabetic cataracts were excluded. We could not compare our surgical time, as there is no literature available on the use of only intracameral lignocaine in patients with cataract with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 47%
“…The pupillary size noted by Nikeghbali et al after intracameral injection of lignocaine was 7.1 mm 23. The pupillary size noted by Gupta et al was 6.9 mm with 0.5% lignocaine and 0.001% epinephrine in routine cataract surgery 33. We did not use epinephrine in irrigating solution.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“… 6 Therefore, additional methods for pupil dilation have been explored. Intracameral injection of mydriatic agents has been shown to be safe and effective, 7 , 8 but was reported to be inferior to conventional topical mydriasis in several studies. 9 , 10 Use of wicks saturated in mydriatic agents has been shown to be comparable to use of drops, but has been associated with an increased risk of conjunctival and corneal abrasions.…”
Section: Introductionmentioning
confidence: 99%
“…A study performed by Gupta et al . [ 1 ] reported that intracameral solution containing 0.5% lignocaine and 0.001% epinephrine provided rapid mydriasis which was adequate for safe topical phacoemulsification cataract surgery, and the dilation achieved was unaffected by other parameters. The mydriasis required for phacoemulsification cataract surgery in this study was achieved by the surgeon himself, using intraoperative intracameral solution, without preoperative topical administration of mydriatics.…”
mentioning
confidence: 99%